Making effective video tutorials: an investigation of online written and video help tutorials in mathematics for preservice elementary school teachers - Gawlik, Christina L. (Kansas State University, 2009)
Online assessments afford many advantages for teachers and students. Okolo (2006) stated, “As the power, sophistication, and availability of technology have increased in the classroom, online assessments have become a viable tool for providing the type of frequent and dynamic assessment information that educators need to guide instructional decisions,” (pp 67-68). As post secondary institutes use online learning environments, education has molded into hybrid experiences. Traditional courses now regularly infuse components of online learning and assessments by required student participation both in person and online. Research is needed to analyze online components of assessment and student achievement. Data was gathered from an undergraduate mathematics course designed for students seeking a bachelor’s degree in elementary education. The course was entitled MATH 320: Mathematics for Elementary School Teachers. Synergies of quantitative and qualitative data were evaluated to assess the impact of written and video help tutorials in online quizzes on student achievement. Three forms of data were collected: student interviews, surveys about students’ online quiz experiences and learning style preferences, and student performance and tutorial usage statistics from seven online quizzes. Student interviews were conducted mid-semester by the researcher who also transcribed and analyzed data. Graphical schemes were used to identify and categorize responses to interview questions. Students’ responses were summarized and quantified in frequency tables. Surveys about students’ online quiz experiences and learning style preferences were analyzed through descriptive statistical methods to describe the data with numerical indices and in graphical form. Correlation matrices and linear regression models were used to identify relationships among survey items. Additionally, Analysis of Variance (ANOVA) techniques were used to explore the data for statistical significance. Students were assigned seven online quizzes throughout the semester. Descriptive statistics were calculated to describe the online quiz data. Regression models were used to determine correlations between use of help tutorials and performance on online quizzes. Data analysis revealed students were persistent and motivated to retake similar quizzes multiple times until a high or perfect score was obtained. After missing a problem, students selected written help tutorials more often than video help tutorials to identify mistakes and understand how to solve the particular problem. The proportion of students whose scores improved after using both written and video help tutorials was greater than those who used the written help tutorials alone. Although the number of students who benefited from the video help tutorials was smaller than expected, the increased performance could be appreciated by students and educators alike. The research presented herein should serve as a base for curriculum development in university mathematics programs utilizing or considering implementation of online tutorials coupled with student evaluation.
Keywords: Mathematics; Online; Tutorials; Video; Assessment; Education, Technology (0710); Education, Tests and Measurements (0288); Mathematics (0405)